HISTORICAL AND GEOGRAPHICAL BACKGROUND OF INVESTMENT IN HALYCHYNA IN THE LATE NINETEENTH – EARLY TWENTIETH CENTURY - Горовий, Олег (Human Geography Journal, 2014)
The article analyzes the historical aspects of the formation of investment in Нalychyna in the late nineteenth – early twentieth century. Revealed major investment attractive industry sector and especially the formation of the investment climate in the Austrian monarchy in Нalychyna. Established, that the main investors of the region were Western European and Austrian companies. Indicated on the role of cooperatives societies «Prosvita», large credit unions and banks in the formation of the region.